Effects of thiopentone, propofol and alfaxalone on laryngeal motion during oral laryngoscopy in healthy dogs. (May 2017) - Smalle, Tesh M.; Hartman, Marthinus J.; Bester, Lynette; Buck, Roxanne K.; Fosgate, Geoffrey T.; Zeiler, Gareth E.
Abstract: Objective: To compare the effects of thiopentone, propofol and alfaxalone on arytenoid cartilage motion and establish the dose rates to achieve a consistent oral laryngoscopy examination. Study design: Randomised crossover study. Animals: Six healthy adult Beagle dogs. Methods: Each dog was randomly administered three induction agents with a 1-week washout period between treatments. Thiopentone (7.5 mg kg −1 ), propofol (3 mg kg −1 ) or alfaxalone (1.5 mg kg −1 ) was administered over 1 minute for induction of anaesthesia. If the dog was deemed inadequately anaesthetised, then supplemental boluses of 1.8, 0.75 and 0.4 mg kg −1 were administered, respectively. Continual examination of the larynx, using a laryngoscope, commenced once an adequate anaesthetic depth was reached until examination end point. The number of arytenoid motions and vital breaths were counted during three time periods and compared over time and among treatments. Data were analysed using Friedman and Mann–Whitney U tests, Spearman rho and a linear mixed model with post hoc pairwise comparison with Tukey correction. Results: The median (range) induction and examination times were 2.8 (2.0–3.0), 2.7 (2.0–3.3) and 2.5 (1.7–3.3) minutes ( p  = 0.727); and 14.1 (8.0–41.8), 5.4 (3.3–14.8) and 8.5 (3.8–31.6) minutes ( p  = 0.016) for thiopentone, propofol and alfaxalone, respectively. The median dose rates required to achieve an adequate anaesthetic depth were 6.3 (6.0–6.6), 2.4 (2.4–2.4) and 1.2 (1.2–1.2) mg kg −1  minute −1, respectively. There was no significant difference for the total number of arytenoid motions ( p  = 0.662) or vital breaths ( p  = 0.789) among induction agents. Conclusion and clinical relevance: The number of arytenoid motions were similar among the induction agents. However, at the dose rates used in this study, propofol provided adequate conditions for evaluation of the larynx with a shorter examination time which may be advantageous during laryngoscopy in dogs.